CORPORATE SUKUK INDONESIA RESPONSE ON MACROECONOMIC CHANGES - Toni Prihandoko; Sunaryati (Universitas Airlangga, 2025)
This study investigates the short-term and long-term responses of changes in macroeconomic variables including exchange rate (EXC), interest rate (IR), inflation (CPI), money supply (JUB), and world oil price (WTI), to the outstanding value of corporate sukuk in Indonesia (SKK) from January 2011 to December 2022. The regression method used is with the Error Correction Model (ECM). The results obtained in this study that in the short term exchange rates, interest rates, inflation, the amount of money in circulation, and the world oil prices have no influence on the outstanding value of Indonesian companies. In the long run, it was found that the exchange rate had a significant negative effect, the money supply had a significant positive influence, while interest rates, inflation and world oil prices did not affect the outstanding value of Indonesian company sukuk.